Federation internationale de football association video gamers' experience of need satisfaction, and their intention to play actual football : the moderating role of perceived competence - Tan, Zi Jian (2016)
The increased pervasiveness of video gaming has led to more interest among researchers in this particular activity in recent years. Several studies on gaming motivation, and its applications have been done using self-determination theory (SDT) as a framework. However, the question of whether this motivation to play sports video games may be translated to perhaps intention to play the actual sport itself remains unanswered. Immersion (level of game realism) was incorporated to see its effects on intention to participate in sports. This study aimed to investigate the extent of psychological needs satisfaction and immersion levels of regular Fédération Internationale de Football Association (FIFA) Online 3 gamers, and whether these variables were able to predict intention to play actual football. Perceived competence (PC) in football was used as moderator for this study. A survey was done on 58 regular FIFA Online 3 gamers. Multiple regression analysis was done on the data. A significant regression equation was found (F(8,49) = 4.510, p < .0005), with an R-squared of .330. Relatedness, immersion (moderated by PC in football), and relatedness (moderated by PC in football) significantly predicted intention to play football (p < .05). It was concluded that competence, autonomy, relatedness, and immersion were able to predict intention to play football, and this relationship was moderated by PC in football. The results also confirmed the generality of the SDT model. Future studies can include standardisation of other variables that may affect intention to participate in sports (e.g. sports involvement, employment status, etc.).